Properties of pre-cast terrazzo tiles and recommended specifications - Karam,G. (2009)
A targeted experimental program was carried out to establish basic reference physical and mechanical properties of commercially available pre-cast marble chip terrazzo tiles and to investigate the effects of varying manufacturing process parameters on those properties. The transverse strength, density, water absorption, and abrasion resistance were measured as a function of casting pressure and residence time in the casting mold for a standard mix design. A simple surface abrasion index test was developed and applied comparing pre-cast terrazzo tiles with reference natural tiling stones. Recommendations for improving existing specifications and developing quality control measures are presented.